2005
DOI: 10.1523/jneurosci.4107-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Mechanisms of Repetition Priming in Occipitotemporal Cortex: Spatiotemporal Evidence from Functional Magnetic Resonance Imaging and Electroencephalography

Abstract: Repeated stimulus presentation (priming) is generally associated with a reduction in neuronal firing, macroscopically mirrored by a decrease in oscillatory electrophysiological markers as well as reduced hemodynamic responses. However, these repetition effects seem to be dependent on stimulus familiarity. We investigate the spatiotemporal correlates of repetition priming in cortical word-recognition networks and their modulation by stimulus familiarity (i.e., words vs pseudowords). Event-related functional mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

24
102
6
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(133 citation statements)
references
References 56 publications
24
102
6
1
Order By: Relevance
“…It can be difficult; therefore, to interpret the absence of correlations between neural repetition effects, as measured by fMRI, and behavioral priming effects. For future studies on this topic, it would be fruitful to perform parallel or simultaneous fMRI and electrophysiological studies (i.e, EEG, ERP, MEG), which have a high temporal resolution (e.g., Fiebach et al, 2005).In conclusion, this study showed that repetition priming of globally familiar and unfamiliar visual objects produces qualitatively different brain patterns of repetition effects. The data are consistent with the view that behavioral priming effects may reflect facilitation at multiple stages along the processing pathway between stimulus and response, including perceptual, semantic, decision, and motor processes.…”
mentioning
confidence: 67%
See 4 more Smart Citations
“…It can be difficult; therefore, to interpret the absence of correlations between neural repetition effects, as measured by fMRI, and behavioral priming effects. For future studies on this topic, it would be fruitful to perform parallel or simultaneous fMRI and electrophysiological studies (i.e, EEG, ERP, MEG), which have a high temporal resolution (e.g., Fiebach et al, 2005).In conclusion, this study showed that repetition priming of globally familiar and unfamiliar visual objects produces qualitatively different brain patterns of repetition effects. The data are consistent with the view that behavioral priming effects may reflect facilitation at multiple stages along the processing pathway between stimulus and response, including perceptual, semantic, decision, and motor processes.…”
mentioning
confidence: 67%
“…Thus, those studies reporting RS for both familiar and unfamiliar stimuli within the same task (van Turennout et al, 2000;Vuilleumier et al, 2002) have found that RS for unfamiliar objects was confined to more posterior regions of occipitaltemporal cortex, whereas RS for familiar stimuli encompassed both posterior and anterior of occipital-temporal regions as well as inferior frontal regions. Similarly, in the context of repetition priming tasks, RE in occipital-temporal regions for unfamiliar stimuli has been reported in very few and relatively small loci, including the anterior fusiform gyrus (Fiebach et al, 2005;Henson et al, 2000;Schacter et al, 1995;Thiel et al, 2002). In addition, Fiebach et al (2005) showed that within the same task, familiar stimuli (words) elicited RS in large areas of occipital-temporal cortex, as well as in frontal and parietal regions, whereas unfamiliar stimuli (pseudowords) produced RE in only a subset of occipital-temporal areas.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 94%
See 3 more Smart Citations